(3eHGOF GdEbJUGOs - (3NGdO CMeO aQMGf(B, (3GdeTgOGfjs; (3QGFO YHO GdNGdb YHO Gddg(B, (3GdYHjOjs ((3YeGf(B:s (3OGQ GdCjGe(B,s, 2015)
(3jVe CSGSjGJ JegjOjI, GdeTcdI GdGbJUGOjI, fXQjI GdWdH h JWhjQgG, fXQjI GdYQV, CSG SjGJ fXQjI GbJUGOjI GOGQjI, GdGfJGL, GdJcGdja h GdGjQGOGJ, GdCShGb h JMOjO GdCSYGQ, fXQjIGdJhRjY, GdONd Gdbhej, GdfbhO h GdeUGQa, GdJLGQI GdNGQLjI, GdJfejI h Gdfeh(B.s
(3GdeUGOQ U(B.221s
Keywords: (3GdEbJUGOs; (3Yde GdEbJUGOs